Bangladesh : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that Bangladesh's external position strengthened considerably in FY2009 and the first four months of FY2010. Strong remittances, resilient exports, and weak imports caused the current account of the balance of payments to record a surplus of almost 3 percent of GDP in FY2009, up from less than 1 percent of GDP in FY2008. Amid continued uncertainty about the strength of the global recovery, Bangladesh's growth momentum is likely to remain somewhat subdued in the near term yet inflation seems set to increase.